Comparison of ab Initio, DFT, and Semiempirical QM/MM Approaches for Description of Catalytic Mechanism of Hairpin Ribozyme - Mlýnský, Vojtěch; Banáš, Pavel; Šponer, Jiří; van der Kamp, Marc W; Mulholland, Adrian J; Otyepka, Michal (Journal of chemical theory and computation, 2014)
We have analyzed the capability of state-of-the-art multiscale computational approaches to provide atomic-resolution electronic structure insights into possible catalytic scenarios of the hairpin ribozyme by evaluating potential and free energy surfaces of the reactions by various hybrid QM/MM methods. The hairpin ribozyme is a unique catalytic RNA that achieves rate acceleration similar to other small self-cleaving ribozymes but without direct metal ion participation. Guanine 8 (G8) and adenine 38 (A38) have been identified as the catalytically essential nucleobases. However, their exact catalytic roles are still being investigated. In line with the available experimental data, we considered two reaction scenarios involving protonated A38H(+) as a general acid which is further assisted by either canonical G8 or deprotonated G8(-) forms. We used the spin-component scaled Møller-Plesset (SCS-MP2) method at the complete basis set limit as the reference method. The semiempirical AM1/d-PhoT and SCC-DFTBPR methods provided acceptable activation barriers with respect to the SCS-MP2 data but predicted significantly different reaction pathways. DFT functionals (BLYP and MPW1K) yielded the same reaction pathway as the SCS-MP2 method. The activation barriers were slightly underestimated by the GGA BLYP functional, although with accuracy comparable to the semiempirical methods. The SCS-MP2 method and hybrid MPW1K functional gave activation barriers that were closest to those derived from experimentally measured rate constants.